Impact of different diets on the survival, pupation, and adult emergence of Culex pipiens biotype molestus larvae, and infectability with the insect-specific Culex Y virus - Hellhammer, Fanny; Heinig-Hartberger, Mareike; Neuhof, Paul; Teitge, Felix; Jung-Schroers, Verena; Becker, Stefanie C. (Frontiers in Tropical Diseases, 2023)
The current rapidly advancing climate change will affect the transmission of arthropod-borne viruses (arboviruses), mainly through changes in vector populations. Mosquitos of the Culex pipiens complex play a particularly prominent role in virus transmission in central Europe. Factors that contribute to the vector population density and the ability of those vectors to transmit viral pathogens (vector competence) can include nutrition during the larval stages. To test the influence of larval diet on larval survival and adult emergence, as well as vector competence, several diets varying in their nutritional composition were compared using a newly established assay. We tested the effects of 17 diets or diet combinations on the fitness of third-instar larvae of Culex pipiens biotype molestus. Larval survival rates at day 7 ranged from 43.33% to 94.44%. We then selected 3 of the 17 diets (Tetra Pleco, as the routine feed; JBL NovoTab, as the significantly inferior feed; and KG, as the significantly superior feed) and tested the effect of these diets, in combination with Culex Y virus infection, on larval survival rate. All Culex Y virus-infected larvae showed significantly lower larval survival, as well as low pupation and adult emergence rates. However, none of the tested diets in our study had a significant impact on larval survival in combination with viral infection. Furthermore, we were able to correlate several water quality parameters, such as phosphate, nitrate, and ammonium concentration, electrical conductivity, and low O2 saturations, with reduced larval survival. Thus, we were able to demonstrate that Culex Y virus could be a suitable agent to reduce mosquito population density by reducing larval density, pupation rate, and adult emergence rate. When combined with certain water quality parameters, these effects can be further enhanced, leading to a reduced mosquito population density, and reduce the cycle of transmission. Furthermore, we demonstrate, for the first time, the infection of larvae of the mosquito Culex pipiens biotype molestus with a viral pathogen.